Self Perceived Emotional Functioning of Spanish Patients with Amyotrophic Lateral Sclerosis: A Longitudinal Study - Mora, Jesus S.; Salas, Teresa; Fajardo, María L.; Ivañez, Lourdes; Rodríguez-Santos, Francisco (Frontiers in Psychology, 2013)
Background: ALS is a neurodegenerative disease of the entire motor system that most frequently ends with respiratory arrest in few years. Its diagnosis and the rapid progression of the motor dysfunctions produce a continued emotional impact. Studies on this impact are helpful to plan adequate psychotherapeutic strategies. Objective: To assess and analyze: 1st: How the patients with ALS perceive their emotional health. 2nd: The emotional impact of their physical disabilities. 3rd: The physical disabilities with highest emotional impact. 4th: The feelings with highest emotional impact. Methods: Up to 110 Spanish patients with ALS were assessed less than one year from diagnosis, then twice more at 6 month intervals, using the ALS Quality of Life Assessment Questionnaire (ALSAQ-40) validated for use in Spanish. Descriptive analysis and correlation between variables were obtained. Results: Worries about the future, of lack of freedom and of being a burden were prevalent feelings. On average depression was felt only ‘sometimes’. Only 25% of the variations in the emotional state were explained by changes in the physical state at first evaluation, and 16% at the last one. Emotional functioning correlated significantly with the physical disabilities at first and second evaluation, less so at third. Communication disabilities always had the highest impact. Depression at first evaluation and hopelessness at the next two evaluations had the highest emotional impact. Hopelessness did not correlate with any physical disability at the third evaluation. On the whole, emotional dysfunction was self perceived as intermediate (between none and worst), and remained stable at one year follow up, in both bulbar and spinal onset patients. Conclusions: Physical dysfunctions per se have a limited role in patients´ emotional distress. Communication disabilities, as well as feelings of depression at early stages of illness, and of hopelessness later on, had the most impact.